جمالية الموت في روايات غسان كنفاني - حاج علي, مازية (قــــــراءات; No 10 (2017): مجلة قراءات, 2019)
ملخص: لاشك أن الموت ظاهرة وصورة تفرض ذاتها على الساحة الفلسطينية، مجسمة أثر موقف ما لفرد أو لجماعة على سيرورة حياة الآخرين، فهناك من يقتل مع سبق الإصرار والترصد ممن يعاديه- الإسرائيلي- وهناك من يموت في سبيل عقيدة يؤمن بها مظهرا هذا الإيمان في رداءة الموت، وهناك من يموت فيختفي في موته القاتل والمقتول... كلها تجليات لحتمية الموت في الأعمال الروائية الخاصة بعالم الأديب غسان كنفاني. Abstract: There is no Doubs  That death is a phenomenon and an image imposes itself on the palestinian arena stereoscoic effect of the position of the individual or of the group of the process of the lives of otheres‚ There are those who are killed with premeditation‚ who ledi-the juif- There are those who die in a matter of doctrine believe in showing this faith in the poor quality of death and there die disappears in his death and the killer almqtol... klha manifestations of the inevitability of death in their own world of writer Ghassan Kanafani novels.